Ammonium in Antarctic Aerosol: Marine Biological Activity Versus Long‐Range Transport of Biomass Burning. Issue 11 (10th June 2021) - Legrand, M.; Weller, R.; Preunkert, S.; Jourdain, B.
Abstract: Year‐round records of the ionic composition of Antarctic aerosol were obtained at the inland Dome C (DC) and coastal Neumayer (NM) sites, with additional observations of black carbon (BC) at NM. Discussions focus on the origin of ammonium in Antarctica. This first Antarctic atmospheric study of several species emitted by biomass burning (BB) indicates that BC and oxalate reach a maximum in October in relation to BB activity in the southern hemisphere. Ammonium reaches a maximum 2 months later, suggesting that BB remains a minor ammonium source there. The ammonium maximum in December coincides with the occurrence of diatom blooms in the austral ocean, suggesting that oceanic ammonia emissions are the main source of ammonium in Antarctica. The ammonium to sulfur‐derived biogenic species molar ratio of 0.15 in summer suggests far lower ammonia emissions from the Antarctic oceans than midlatitude southern oceans. Plain Language Summary: There are still uncertainties on the magnitude of natural ammonia emissions into the atmosphere, in particular the contribution of oceans with respect to soils and open fires. Biomass burning (BB) plays an important role in the Earth system and there is a need to reconstruct past fire activity. Studying charcoals in lake sediments and various impurities in ice cores can do this. Most species emitted by BB including ammonium have, however, other noncombustion sources, motivating simultaneous investigation of several potential fire proxies in ice archives. We report on multiple‐year records of atmospheric aerosol obtained in Antarctica for which ammonium together with proxies of BB and biogenic oceanic emissions were analyzed. It is shown that, even if ammonia emissions from the polar ocean are lower than those from the midlatitude oceans, the southern ocean is the main source of ammonium in Antarctica. This first Antarctic atmospheric study of several species emitted by BB indicates that black carbon, oxalate, potassium, but likely not ammonium, present in Antarctic ice may help to reconstruct past BB from continents of the southern hemisphere. Key Points: First atmospheric study conducted in Antarctica of species emitted by biomass burning including black carbon, oxalate, and fine potassium Black carbon and oxalate aerosol peak in October at the coastal Antarctic site of Neumayer in relation with South America biomass burning Ammonium aerosol peaks in December and biogenic sulfur aerosol in January, consistent with NH3 and DMS emissions in the austral ocean